Hukum Merokok dalam Islam: Analisis Perbandingan Nahdlatul Ulama dan Muhammadiyah - Fathurrohman Nur Hidayat; Rendy Aprilio Sulaiman; Jelita Tibyana Shidqy; Nazwa Angrraeni; Ester Aprilia Diyan Sari; Baidhowi (STIKes Ibnu Sina Ajibarang, 2025)
This study examines the comparative fatwas of Muhammadiyah and Nahdlatul Ulama (NU) regarding the Islamic legal ruling on smoking in the Indonesian context. The research employs a qualitative method through a literature-based analysis of official documents, academic journals, and decisions from Bahtsul Masā’il and the Majelis Tarjih dan Tajdid. The findings indicate that Muhammadiyah declares smoking as prohibited (ḥarām) because it contradicts the objectives of Islamic law (maqāṣid al-syarī‘ah), particularly in preserving life (ḥifẓ al-nafs) and wealth (ḥifẓ al-māl). Conversely, NU categorizes smoking as reprehensible (makrūh) on the basis that no definitive textual evidence explicitly forbids it, while also considering socio-economic factors within society. Muhammadiyah adopts a normative-preventive approach, whereas NU emphasizes a cultural-educational one. The difference between the two fatwas reflects not a contradiction but a constructive ikhtilāf, enriching the diversity of Islamic jurisprudence in Indonesia.